(3dhYI GdTGcj hOeYI GdHGcjs - (3GdOeTbj, NGOe GdTjN QSdGf, efUhQ Hf YHO GdQMef, J(B967(3g`s
(3ChdgG (B:s
(3hUdi Gddg Ydi SjOfG eMeO hBdg hdGHO ef Tchi Edi Pj eQhI jhGSjc Ch jSdjc Ch jJhLY, CeG HYO MeOG ddg GdPj bVi HGdeMHI hGdhdhY hMce HEMQGb cHO cd YGTb hhdhYs
(3BNQgG (B:s
(3hde Jcf cGdYGTb GdeScjf jfhM Ydi ZUf GdbhGe hjHcj Ydi NUQ hOOa aj gPG GdeYfi eG jahb GdeZfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 7 / 300s
(3eYLe GdeDdajf(B: 3 / 916s
(3cTa GdXfhf(B: 2 / 1570s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdCOHs